The Growing Incidence of Bullous Pemphigoid: Overview and Potential Explanations - Kridin, Khalaf; Ludwig, Ralf J. (Frontiers in Medicine, 2018)
Bullous pemphigoid (BP) is the most common type of subepidermal autoimmune bullous diseases. BP characteristically affects the elderly and is seen mainly in patients older than 70 years. While the annual incidence of BP has been estimated to be between 2.4 and 23 cases per million in the general population, it rises exponentially to 190 to 312 cases per million in individuals older than 80 years. In addition, a growing body of evidence reports a remarkable trend of increased incidence of BP, showing a 1.9- to 4.3-fold rise over the past two decades. This demonstrable increase warrants a higher awareness of the increased risk to develop BP. This review summarizes the current understanding of the epidemiological features of BP and sheds light on the putative explanations for its growing incidence.